Covid-19 and the Decline in Investment in West Nusa Tenggara: Indonesia - Dewayani, Eka Kadharpa Utama; Ginting, Yanti Mayasari; Azizurrohman, Muhammad; Pramuja, Risky Angga (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research examines the effects of the COVID-19 pandemic on investment in West Nusa Tenggara (NTB), Indonesia. Using a combination of quantitative data from the Republic of Indonesia's Investment Coordinating Board and qualitative data from the Head of the Office of Investment and One Stop Integrated Services, the study investigates investment realization by district and city, sector, and investor's country of origin. The analysis reveals that even prior to the COVID-19 outbreak, investment levels in NTB were declining due to a series of natural disasters, including an earthquake in 2018. The pandemic further exacerbated the decline in investment, with many investors opting to delay their investments in the region. However, some sectors such as mining, tourism, and transportation showed improvements during the period. The findings highlight the challenges faced by West Nusa Tenggara in attracting investment and achieving regional development goals. The study emphasizes the importance of understanding a region's potential and creating favorable investment conditions to stimulate economic growth. Keywords: Covid-19, Investment, NTB